A Preliminary Investigation of Cases of Reincarnation among the Beaver and Gitksan Indians - Mills, Antonia (Anthropologica, 2022)
The author describes belief in and cases of reincarnation among two different groups of Indians in northern British Columbia, Canada, the Beaver and the Gitksan, and gives illustrative examples in which a child is identified as a particular person returned. The differences in belief, e.g. belief in cross-sex reincarnation among the Beaver, and multiple reincarnation of one person among the Gitksan, are examples of cultural conditioning, although the author posits that belief in reincarnation is endemic in shamanic societies and concludes that while the cases do not demonstrate that reincarnation actually takes place, case oriented studies gather valuable data which needs to be assessed.